REDUCTION OF WHITE CORN (ZEA MAIZE IPB VAR. 6) DEPENDENCY ON INORGANIC FERTILIZER THROUGH VAMRI AND BIO-N INOCULATION - Pascual, Pet Roey L.; Monsalud, Florentino C.; Monsalud, Rosario G.; Brown, Marilyn B. (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 2, 2015, 2018)
Please see PDF file.